2023
DOI: 10.1186/s13018-023-03500-6
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal patellar loading may lead to femoral trochlear dysplasia: an experimental study of patellar hypermobility and patellar dislocation in growing rats

Abstract: Background This animal study aimed to explore the effects of patellar hypermobility and patellar dislocation on the developing femoral trochlea. Methods Seventy-two 3-week-old Wistar rats were randomly divided into three groups. The sham group (SG) underwent simple incision and suture of the skin and subcutaneous tissue; the patellar hypermobility group (PHG) underwent medial and lateral retinacular release and pie-crusting technique for the patell… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The explanation for this in previous studies [19, 20, 33, 37] is that the lack of stress stimulation to the medial condyle in the laterally dislocated patella leads to delayed development of the medial condyle, resulting in dysplasia of the medial trochlea. Thus, osteogenesis of the epiphyseal plate is affected by mechanical stress [7, 33, 35] and influences the formation of trochlear morphology, which may be an important intermediate link in the development of trochlear dysplasia.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The explanation for this in previous studies [19, 20, 33, 37] is that the lack of stress stimulation to the medial condyle in the laterally dislocated patella leads to delayed development of the medial condyle, resulting in dysplasia of the medial trochlea. Thus, osteogenesis of the epiphyseal plate is affected by mechanical stress [7, 33, 35] and influences the formation of trochlear morphology, which may be an important intermediate link in the development of trochlear dysplasia.…”
Section: Discussionmentioning
confidence: 95%
“…The explanation for this in previous studies [19,20,33,37] is that the lack of stress stimulation to the medial condyle in the laterally dislocated patella leads to delayed development of the medial condyle, resulting in dysplasia of the medial trochlea. Thus, osteogenesis of the epiphyseal plate is afected by mechanical stress [7,33,35] and inluences the formation of trochlear morphology, which may be an important intermediate link in the development of trochlear dysplasia. It was found that there are signiicant positive correlations among the area of the medial growth plate, medial TPD, height of the medial condyle and capacity of the proximal trochlear groove, which consistent with previous indings.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Trochlear dysplasia may result from insufficient loading patterns in the patellofemoral joint secondary to hyperlaxity. 39 There was a statistically significant increase in patellar height and tilt in patients who had failed isolated MPFLR in our cohort. A cautious approach is warranted when correction of the patellar tilt is considered in patients with hyperlaxity, as lateral retinacular release can lead to iatrogenic medial instability.…”
Section: Discussionmentioning
confidence: 50%
“…The correlations between distal torsion and dysplastic anterior condyles and trochlea may be due to the abnormal mechanical stimuli that are applied to the anterior condyles and trochlea, which may be caused by increased distal torsion [13, 27]. Liao et al [14] reported that the internal rotation of the femur resulted in a significantly higher octahedral shear stress and hydrostatic pressure.…”
Section: Discussionmentioning
confidence: 99%